Study on the permeability coefficient model of salinized frozen soil based on unfrozen water content curve - Liu, Gunag; Zhang, Zhilong; Cheng, Zhe; Hao, Ge; Hao, Yufeng; Fu, Ting (Frontiers in Earth Science, 2023)
Due to the fact that the permeability coefficient of salinized permafrost is difficult to measure through experimental test, this paper develops a model of the permeability coefficient of salinized permafrost by using SFCC curves, which takes into account the effects of velocity slip on pore wall and seepage of unfrozen water film. This model is on the basis of capillary bundle model, and combines with phase diagram theory of water-salt binary system. For the silty clay from Qinghai-Tibet Plateau and silts from Onedia city, the permeability coefficient fluctuation vs temperature is calculated using the model. The estimated calculations of the permeability coefficient model were all found to be in good agreement with the experimental data by comparison, which confirmed the validity of this model. Additionally, the variation trend of permeability coefficient of NaCl, Na2SO4, and Na2CO3 type saline soils containing different salt contents is examined. Results indicate that before saline soils freeze, NaCl does not crystallize in the pores and thus has little impact on the permeability coefficient of saline soils, whereas Na2SO4 and Na2CO3 both crystallize and block the pores and therefore have a greater impact, and the permeability coefficient decreases more rapidly with the increasing salt content. Once the soils have frozen, the freezing temperature has a larger impact on the permeability coefficient of saline soils. During the early stage of freezing, the lower the freezing temperature is, the larger the permeability coefficient is. In the late stage of freezing, the permeability coefficients of saline soils with various salt contents tended to be the same.